Orientación psicopedagógica y su incidencia en el desarrollo socioemocional de los estudiantes de 5° año EGB de la UE 24 de mayo de la Parroquia San Juan, periodo 2024-2025 - Aldaz Muñoz, Lizeth Thalia (2025)
The main objective of this project is to analyze how psychopedagogical guidance impacts the socioemotional development of students, promoting their emotional well-being and strengthening their social and self-regulation skills. It is based on the recognition that socioemotional development is an essential component of comprehensive learning and academic success, and that psychopedagogical guidance plays a key role in providing strategies and support to address these areas. The purpose of this work was to identify that students face multiple emotional and social challenges on a daily basis that can negatively influence their academic performance and their adaptation to the school environment. The lack of tools to manage emotions, resolve conflicts or work as a team can lead to poor performance, demotivation and difficulties in interpersonal relationships. This project focuses on identifying how psychopedagogical intervention can address these needs and generate a positive impact on socioemotional development. The project hopes to confirm that psychopedagogical guidance has a significant impact on the socioemotional development of students, promoting their emotional well-being, social interaction and academic performance. The aim is also to generate replicable strategies that can be implemented in different school contexts, promoting a comprehensive approach to education.